Level I academic trauma center integration as a model for sustaining combat surgical skills. Issue 6 (June 2015) - Hight, Rachel A.; Salcedo, Edgardo S.; Martin, Sean P.; Cocanour, Christine S.; Utter, Garth; Galante, Joseph M.
<x xml:space="preserve">Abstract</x> INTRODUCTION As North Atlantic Treaty Organization (NATO) countries begin troop withdrawal from Afghanistan, military medicine needs programs for combat surgeons to retain the required knowledge and surgical skills. Each military branch runs programs at various Level I academic trauma centers to deliver predeployment training and provide a robust trauma experience for deploying surgeons. Outside of these successful programs, there is no system-wide mechanism for nondeploying military surgeons to care for a high volume of critically ill trauma patients on a regular basis in an educational environment that promotes continued professional development. We hypothesize that fully integrated military-civilian relationship regional Level I trauma centers provide a surgical experience more closely mirroring that seen in a Role III hospital than local Level II and Level III trauma center or medical treatment facilities. METHODS We characterized the Level I trauma center practice using the number of trauma resuscitations, operative trauma/acute care surgery procedures, number of work shifts, operative density (defined as the ratio of operative procedures/days worked), and frequency of educational conferences. The same parameters were collected from two NATO Role III hospitals in Afghanistan during the peak of Operation Enduring Freedom. Data for two civilian Level II trauma centers, two civilian Level III trauma centers, and a Continental United States Military Treatment Facility without trauma designation were collected. RESULTS The number of trauma resuscitations, number of 24-hour shifts, operative density, and educational conferences are shown in the table for the Level I trauma center compared with the different institutions. Civilian center trauma resuscitations and operative density were highest at the Level I trauma center and were only slightly lower than what was seen in Afghanistan. Level II and III trauma centers had lower numbers for both. The Level I trauma center provided the most frequent educational opportunities. CONCLUSION In a Level I academic trauma center integrated program, military and civilian surgeons have the same clinical and educational responsibilities: rounding and operating, managing critical care patients, covering trauma/acute care surgery call, and mentoring surgery residents in an integrated residency program. The Level I trauma center experience most closely mimics the combat surgeon experience seen at NATO Role III hospitals in Afghanistan compared with other civilian trauma centers. At high-volume Level I trauma centers, military surgeons will have a comprehensive trauma practice, including dedicated educational opportunities. We recommend integrated programs with Level I academic trauma centers as the primary mechanism for sustaining military combat surgical skills in the future.